In situ tailoring solid electrolyte interphase of three‐dimensional Li metal electrode for enhanced Coulombic efficiency - Jiang‐Peng Wang; Feng Lang; Quan Li (EcoMat, 2023)
Abstract Although three‐dimensional (3D) lithium metal electrode is effective in restricting the Li dendrite growth upon cycling, problems associated with the unstable electrode/electrolyte interphase become more severe due to increased interfacial area that is intrinsic of the 3D structures, being a major cause for the low Columbic efficiency. While building a desirable solid electrolyte interphase (SEI) serves as an effective solution to improve the electrode/electrolyte interfacial stability, the 3D nature of the electrode makes the task challenging. In the present work, we demonstrated the in‐situ formation of SEI on chemically/structurally modified carbon cloth that is used as the 3D host electrode for Li metal. Here we show that ZnS/ZnO nanotube arrays uniformly grown on the carbon cloth served as precursors for the in‐situ formation of Li2S/Li2O/LiZn containing artificial SEI in the first lithiation process. While Li2S and Li2O are preferred components in SEI, the in situ generated Zn functions as a lithiophilic site that guides the uniform lithium deposition upon repeated charging/discharging process. As a result, symmetric cells adopting the O‐, S‐, and Zn‐ modified 3D anode demonstrate significantly improved Coulombic efficiency (99.2% over 400 cycles at 1 mA cm−2/1 mA h cm−2). Furthermore, the Li/ZSONT/CC//LiFePO4 full cell shows a capacity retention of 71% after 4000 cycles at 2C. The present work sheds light on effective design strategies for SEI formation on a 3D electrode host with controllable SEI composition.